Effect of Different Irrigation Levels on Water Requirement, Water Use Efficiency and Cost Analysis of Strawberry under Silver Black Mulch - MANE, M.S.; OMKAR, KHADAS; PATIL, S.T.; DHEKALE, J. S.; INGLE, P.M.; BHANGE, H.N. (Journal of the Indian Society of Coastal Agricultural Research, 2023)
The present study was aimed with specific objectives to study the effect of different irrigation levels on water requirement, water use efficiency and cost analysis of strawberry. The research was carried out at Research Farm of Department of Irrigation and Drainage Engineering, College of Agricultural Engineering and Technology, Dr. Balasaheb Sawant Konkan Krishi Vidyapeeth, Dapoli, during 12th December 2013 to 2nd April 2014. The experiment was laid out with twenty treatment combinations and conducted using randomized block design (RBD) with four replications. There were five levels of irrigation viz. I1 (0.4PE), I2 (0.6PE), I3 (0.8PE), I4 (1.0 PE), and I5 (1.2PE). The irrigation was scheduled on daily basis. The total depth of water applied in irrigation levels I1, I2, I3, I4 and I5 were 24.54 cm, 36.81 cm, 49.09 cm, 61.36 cm and 73.63 cm, respectively which saved 66.6 per cent, 50.0 per cent, 33.3 per cent and 16.7 per cent water over the irrigation level I5. The maximum water use efficiency was found in treatment I1 (4.28 q ha-1 cm-1) followed by I2 (3.78 q ha-1 cm-1), I3 (2.77 q ha-1 cm-1), I4 (2.12 q ha-1 cm-1) and I5 (1.38 q ha-1 cm-1), respectively. The maximum net income of Rs. 10, 92,496 per hectare was recorded in treatment I2 followed by Rs. 10, 50,188, Rs. 9, 77, 868 and Rs. 6, 82, 417 in treatment I3, I4 and I1, respectively. In irrigation level I5 the net income of Rs. 6, 37, 948 per hectare was observed, which was lowest amongst all other treatments. The maximum B: C ratio of (2.88) was observed in irrigation level I2 followed by I3 (2.80), I4 (2.67) and I1 (2.18). The minimum B: C ratio was observed in irrigation level I5 (2.09) which was due to lowest yield.